2018
DOI: 10.1016/j.marpol.2018.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the demand for aquaculture insurance: An investigation of fish farmers' willingness to pay in central coastal areas in China

Abstract: Despite the remarkable development in its fishery sector, the penetration rate of fishery insurance in China is considerably low. This paper examines the key factors that contribute to the poor performance of fishery insurance, in particular aquaculture insurance, in China. The doublebounded dichotomous choice contingent valuation method (DB DCCVM) is used to investigate fish farmers' willingness to pay (WTP) for insurance, based on a survey of 1,280 fish farmers in three coastal cities in China. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
2
15
2
Order By: Relevance
“…The mean participation in aquaculture insurance and amount WTP were 0.657 and GH¢ 241.667 (US$ 50.00) Profitability of aquaculture insurance respectively. In contrast, Zheng et al (2018) revealed that the mean amount WTP for aquaculture insurance in China was US$ 90.05. A plausible reason could be that farmers in China had higher income levels relative to Ghanaian farmers.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The mean participation in aquaculture insurance and amount WTP were 0.657 and GH¢ 241.667 (US$ 50.00) Profitability of aquaculture insurance respectively. In contrast, Zheng et al (2018) revealed that the mean amount WTP for aquaculture insurance in China was US$ 90.05. A plausible reason could be that farmers in China had higher income levels relative to Ghanaian farmers.…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, Watson et al (2018) examined cooperative insurance for aquaculture in Myanmar. Further, Zheng et al (2018) evaluated the Profitability of aquaculture insurance willingness to pay for aquaculture insurance in China whiles Han and Jiang (2019) analysed the insurance for Mariculture in China. However, to the best of our knowledge, there appears to be no empirical study on the prospects, determinants, and profitability of aquaculture insurance in Africa, particularly Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…The participation rate of marine farmers who join cooperatives is only 33.06%. The fishery in developing countries is mostly managed by fishermen or small-scale fishing farmers [88], who will suffer great losses by climate disasters and who should be protected by the fishery insurance. But due to the fact that most of these fishermen or farmers often live and work separately, they find it hard to get their preferred insurance from the private insurance companies.…”
Section: (12) Unpaid Productive Loan and Insurance Participationmentioning
confidence: 99%
“…8 Biochar is a kind of carboncontaining, stable and highly aromatized carbonaceous solid material prepared by pyrolysis of biomass (e.g., plant residues, livestock and poultry manure, and other organic solid wastes) under oxygen-limited conditions and the temperature below 700 C. [8][9][10] In recent years, China supplies about 60.5% of aquatic products worldwide. 11,12 The large amount of wastes (e.g., dead or sick aquatic carcasses, residual baits and feces) that produced during the intensive farming process are burned or buried, which will cause not only waste of biomass energy and environmental pollution, but also risks of zoonotic diseases. 11,12 Alternatively, if these wastes were converted into biochar and employed for the removal of heavy metal ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The large amount of wastes (e.g., dead or sick aquatic carcasses, residual baits and feces) that produced during the intensive farming process are burned or buried, which will cause not only waste of biomass energy and environmental pollution, but also risks of zoonotic diseases. 11,12 Alternatively, if these wastes were converted into biochar and employed for the removal of heavy metal ions (e.g. Zn 2+ ) from wastewater, it would be quite benecial to resource utilization of waste and remediation of heavy metal polluted wastewater.…”
Section: Introductionmentioning
confidence: 99%